2022
DOI: 10.1192/bjo.2022.559
|View full text |Cite|
|
Sign up to set email alerts
|

Exhaustion disorder: scoping review of research on a recently introduced stress-related diagnosis

Abstract: Background Symptoms related to chronic stress are prevalent and entail high societal costs, yet there is a lack of international consensus regarding diagnostics and treatment. A new stress-related diagnosis, exhaustion disorder, was introduced into the Swedish version of ICD-10 in 2005. Since then, use of the diagnosis has increased rapidly. Aims To create the first comprehensive synthesis of research on exhaustion disorder to report on the current state of knowledge. Preregistration: Op… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 119 publications
(291 reference statements)
4
22
0
Order By: Relevance
“…, and the proportion of women in the present study is similar to what has been found in previous clinical trials on ED(Lindsäter et al, 2022). Recruitment was largely carried out online, which likely introduces some selection bias, and even though recruited individuals represented a geographical spread that largely corresponds to population size of different Swedish regions, most participants were from larger cities.…”
supporting
confidence: 74%
See 2 more Smart Citations
“…, and the proportion of women in the present study is similar to what has been found in previous clinical trials on ED(Lindsäter et al, 2022). Recruitment was largely carried out online, which likely introduces some selection bias, and even though recruited individuals represented a geographical spread that largely corresponds to population size of different Swedish regions, most participants were from larger cities.…”
supporting
confidence: 74%
“…The 10-item Perceived Stress Scale (PSS-10; Cohen et al, 1983) is the most common measure of perceived stress used in clinical trials of stress-related ill health (Estevez Cores et al, 2021;Svärdman et al, 2022) and measures how often one has perceived life as unpredictable, uncontrollable, and overloading in the past month (scale range 0-40). A higher score indicates higher level of perceived stress.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review of all published empirical ED studies found that research on the validity of this new diagnosis remains limited (5). The clinical picture of ED is similar to that of burnout (6, 7) and chronic fatigue (8), and the overlap with anxiety and depressive disorders is substantial (5).…”
Section: Introductionmentioning
confidence: 99%
“…A recent review of all published empirical ED studies found that research on the validity of this new diagnosis remains limited (5). The clinical picture of ED is similar to that of burnout (6, 7) and chronic fatigue (8), and the overlap with anxiety and depressive disorders is substantial (5). Amidst an international debate regarding whether burnout should be conceptualized as a medical disorder (9), ED has not been included in international versions of the ICD or the Diagnostic and Statistical Manual of Mental Disorders (DSM).…”
Section: Introductionmentioning
confidence: 99%